Pumping a 100–600 Pa yield stress clay slurry with a centrifugal pump - Furlan, JM; Visintainer, RJ; Sellgren, A (Paste 2013: 16th International Seminar on Paste and Thickened Tailings, 2013)
The pumping of simulated and authentic thickened tailings or paste slurries with centrifugal pumps has been reported from loop tests at the GIW Hydraulic Laboratory, USA. A tendency of a backward sloping head curve for flow rates less than about 50% of the best efficiency region (BEP) has been observed when the solids concentration by volume approaches 50% for authentic tailings slurries. Recent loop testing during froth pump development work has addressed air binding or air lock effects in detail. Despite careful considerations during tailings testing, successive build-up of an air pocket may be the cause of observed difficulties to maintain the head for low flow rates in some cases. An arrangement to remove entrained air in the tank feeding of a standard closed 0.31 m diameter closed impeller pump showed that a phosphate clay slurry with Bingham yield stresses from about 100–600 Pa could be pumped for low flow rates up to about 50% of BEP giving a forward sloping head curve with a derating pattern typical of highly viscous Newtonian fluids. Tailings products often have a considerable portion of particles larger than 75 µm. The two-component behaviour compared to clays calls for a repeated test now with authentic tailings. Thickened tailings derating modelling approaches covering a large span of flow rates are briefly discussed in relation to various factors influencing the tendencies of a backward sloping head curve.